English language learners and kindergarten entry age: Achievement and social-emotional effects. Issue 4 (3rd July 2016) - Gottfried, Michael; Le, Vi-Nhuan; Datar, Ashlesha
ABSTRACT: In evaluating the role of kindergarten entry age, previous researchers have not examined the entry-age effects for English language learners (ELL). Additionally, little work has assessed the role of entry age on both achievement and social-emotional outcomes. This study is the first to do both simultaneously. The authors used data from a longitudinal study that followed a national sample of U.S. students from kindergarten through Grade 5. Relying on variation in children's birth dates and in states' kindergarten entrance age cutoffs, the authors estimated how differences in the age at which children enroll in kindergarten are related to their achievement and social-emotional outcomes. Our results show that enrolling in kindergarten as an older entrant is associated with significantly higher achievement and social-behavioral outcomes during the early elementary school years for ELL students, but that these effects largely disappear by the end of elementary school. Policy implications are addressed.